Structure analysis of semi submarine bulkhead / Muhammad Ikhwan Naim Zakaria - Zakaria, Muhammad Ikhwan Naim (2006)
This project required the studies on analysis of submarine bulkhead using the finite element method. A simple submarine bulkhead modeling was built in finite element method. The stress in the submarine bulkhead will be determined by formulation. From the formulation, the stress at the keel and at the top of the submarine bulkhead will be calculated and compared with the result in finite element method. The prediction of stress in submarine bulkhead structure will be obtained by ANSYS, finite element software.